Epicardial signalling in mammalian heart regeneration - Masters, M (2015)
Whilst lower vertebrate species, such as newt and zebrafish, can regenerate their hearts following substantial injury throughout life, humans and other adult mammals undergo cardiac scarring and remodelling in response to myocardial infarction (MI), which leads to chronic heart failure. However, recent work has identified a 'regenerative window' in mammals such that the 1 day-old mouse (P1) was able to regenerate lost myocardium following MI induced by ligation of the left anterior descending coronary artery (LAD) within three weeks, but an equivalent injury sustained on or after P7 resulted in adult-like wound healing. These findings suggest that developmental cues may be instructive towards regeneration. The epicardium, the outer mesothelial lining of the heart, is an important source of cardiovascular cells and signals that respectively contribute directly to the major lineages of the forming heart and instruct muscle growth during heart development. Under normal conditions, the epicardium is quiescent in the adult heart, but is activated upon injury and can be ectopically stimulated to contribute to neovascularisation and myocardial repair in infarcted adult mouse hearts. Furthermore, organ-wide activation of the epicardium underpins zebrafish heart regeneration, functioning, in part, to contribute a vascular niche and regulate cardiomyocyte cell-cycle re-entry and proliferation. We, therefore, hypothesised that epicardial signalling may also influence heart regeneration in neonatal mice. The aims of this project were to 1) establish the neonatal MI injury model in-house; 2) confirm and characterise neonatal mouse heart regeneration by magnetic resonance imaging (MRI) and 3) investigate the role(s) of the epicardium and epicardial signalling in mammalian heart regeneration. In addressing these aims, novel anaesthetic and aseptic protocols were designed to refine cardiothoracic surgery in neonatal mice and establish the injury model. A protocol for MRI assessment of heart regeneration in neonatal mice was also established. Consistent with previous reports, we observed significant, although incomplete myocardial regeneration after 21 days with limited anterior wall scarring when MI was induced at P1, compared to significant collagen deposition and remodelling following MI at P7. Epicardial potential was lost coincident with closure of the 'regenerative window' and the epicardial response following injury induced at regenerative (P1) and reparative (P7) time-points was documented via retinoic acid signalling as a key developmental epicardial mitogen. This work furthers our understanding of the cell and molecular mediators of regeneration in neonatal mice, and may lead to therapeutic strategies for amplifying the regenerative response of adult mammalian hearts to injury.